2009
DOI: 10.1111/j.1365-2710.2009.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple therapy with ecabet sodium, omeprazole, amoxicillin and metronidazole is effective for eradication of Helicobacter pylori after failure of first-line therapy (KDOG0201 Study)

Abstract: Quadruple therapy including ecabet sodium is useful as second-line eradication treatment for H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…A recent Japanese study also showed a high eradication rate with similar, 2-week, second-line therapy of omeprazole, amoxicillin, metronidazole, and ecabet sodium (a mucoprotective agent) (96% (50 ⁄ 52) by ITT analysis and 98% (50 ⁄ 51) by PP analysis) [22]. A recent Japanese study also showed a high eradication rate with similar, 2-week, second-line therapy of omeprazole, amoxicillin, metronidazole, and ecabet sodium (a mucoprotective agent) (96% (50 ⁄ 52) by ITT analysis and 98% (50 ⁄ 51) by PP analysis) [22].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A recent Japanese study also showed a high eradication rate with similar, 2-week, second-line therapy of omeprazole, amoxicillin, metronidazole, and ecabet sodium (a mucoprotective agent) (96% (50 ⁄ 52) by ITT analysis and 98% (50 ⁄ 51) by PP analysis) [22]. A recent Japanese study also showed a high eradication rate with similar, 2-week, second-line therapy of omeprazole, amoxicillin, metronidazole, and ecabet sodium (a mucoprotective agent) (96% (50 ⁄ 52) by ITT analysis and 98% (50 ⁄ 51) by PP analysis) [22].…”
Section: Discussionmentioning
confidence: 90%
“…AST or ALT value was elevated in 5 (8%) of 65 patients, but the elevation was also mild (AST values prior to treatment, 1 and 2 week later, 20 ± 3 (range, [16][17][18][19][20][21][22], 35 ± 10 (23-43), and 47 ± 4 (42-50) IU ⁄ L; and ALT, 20 ± 3 (18-23), 37 ± 8 (30-45), and 64 ± 13 (48-77) IU ⁄ L, respectively). Although the elevation was mild (AST, from 28 ± 4 (range, 23-35) to 52 ± 14 (33-81) IU ⁄ L; and ALT, from 32 ± 12 (17-60) to 59 ± 19 (39-103) IU ⁄ L), they discontinued therapy for safety.…”
Section: Blood and Urine Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 61 arms (30%) showed PP cure rates >90% . Two studies (two arms) evaluated a dual therapy (rabeprazole and amoxicillin), 34 arms evaluated a triple therapy (Table ), and 25 arms evaluated quadruple therapies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…16 Infection by this bacterium could potentially result in various gastroduodenal diseases such as peptic ulcer, functional dyspepsia, MALT lymphoma, and [23][24][25] compare the accuracy of the UBT to several other invasive diagnostic tests such as gastric biopsies performed during endoscopy (rapid urease test, histology, culture) and a large number of papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have focused on the efficacy of eradication therapy and the selection of alternate therapies. 16 Infection by this bacterium could potentially result in various gastroduodenal diseases such as peptic ulcer, functional dyspepsia, MALT lymphoma, and [23][24][25] compare the accuracy of the UBT to several other invasive diagnostic tests such as gastric biopsies performed during endoscopy (rapid urease test, histology, culture) and a large number of papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%